Modulateur PWM Numerique Programmable : Application a la Conversion d'energie Maximale du panneau solaire a la batterie - Y. Haroen; J. Jalade; J.C. Marpinard (Journal of Mathematical and Fundamental Sciences, 1986)
Abstract. PWM modulator with feedback analog is often used in a voltage/current control system, but sometimes problems arise in which the modulator could not be used with this method. To overcome this problem a programmed numeric PWM modulator is used. This paper discusses the working procedure and realization from the software and hardware point of yiew by using 8085 microprocessor. One of its application is to control the firing time of power switching transistor in a DC converter (BUCK) where the input BUCK is connected to the solar cell panel and the output side is connected to the battery. With time firing control of the power transistor, the power of the solar cell panel can be transferred to the battery at its maximum. Sari. Modulator PWM dengan umpan balik analog sering digunakan dalam sistem pengaturan tegangan/arus, tetapi kadang-kadang hal ini menimbulkan masalah, sehingga modulator dengan cara ini tidak dapat dipergunakan lagi. Salah satu cara untuk mengatasinya adalah dengan menggunakan modulator PWM numerik terprogram. Di sini diuraikan cara kerja dan realisasinya ditinjau dari piranti lunak dan piranti keras dengan menggunalan mikroprosessor 8085. Salah satu aplikasinya adalah pengaturan waktu penyalaan transistor daya switching pada suatu konverter arus searah (BUCK). Sisi masukan BUCK dihubungkan ke suatu panel sel surya dan sisi keluaran dihubungkan ke baterai. Dengan pengaturan waktu penyalaan transistor daya, maka daya dari panel sel surya dapat ditransfer semaksimum mungkin ke dalam baterai.